Completion of Legal Conflicts in The Implementation of The Decision of the National Sharia Arbitration Board - Sofyan al-Hakim; Muhammad Hasanuddin; Heris Suhendar (UIN Sunan Gunung Djati Bandung, 2020)
The background of the article is the contents of Article 59 paragraph (3) and explanation of paragraph (1) of the Law on Judicial Power. The article authorizes the District Court to implement the decision of the Sharia arbitration body on the resolution of Islamic economic disputes. The article and explanation of the verse contradicts the absolute authority of the Religious Courts regulated in Article 49 letter (i) of the Law on Religious Courts. This shows that, the legislators are not consistent in making laws and regulations, so that it creates legal uncertainty. By applying the normative legal research method to the statute approach and case approach, this article seeks to describe the phenomenon of legal conflicts that occur. From the in-depth analysis it can be concluded that the legal provisions regarding the implementation of the decision of the National Sharia Arbitration Board are regulated in the Arbitration Law, the Judicial Power Act and the Religious Courts Act. The legal substance of the provisions therein enables antinomy or legal conflicts. Antinomy settlement can use the principle of lex specialis derogat legi generali